Carburizing of Ti–6Al–4V alloy: Structure, growth mechanism and wear performance - He Zhang; Shigang Zhang; Mingjun Zhang; Jian An (Journal of Materials Research and Technology, 2023)
Ti–6Al–4V alloy was pack carburized at temperatures of 950–1100 °C within a holding time range of 1–10 h. The structures and constituent phases of carburized layers were analyzed by optical microscope, scanning electron microscope (SEM) and X-ray diffraction (XRD). The structure of carburized layer was strongly influenced by carburizing temperature, it mainly consisted of a transition zone sub-layer of α-Ti (C) solid solution at 950 °C, and a compound (Ti-carbides + Ti-intermetallics) sub-layer as well as a transition zone sub-layer at temperatures of 1000–1100 °C. The growth of compound sub-layer was controlled by the growth of Ti–Al intermetallics and chemical reaction between C and Ti–Al intermetallics, and the growth of compound sub-layer required a gestation period depending on carburizing temperature. The growth kinetics of compound sub-layers followed a parabolic law beyond gestation period, from which the diffusion activation energy was calculated to be 192.597 kJ/mol. Carburizing of Ti6Al–4V alloy leads to a reduction of over 96.16 % in wear rate, and the wear resistance is enhanced with increasing carburizing temperature.